Temperature Sensing - Stanimirovi?, Ivanka; Stanimirovi?, Zdravko (IntechOpen, 2018)
Temperature is the most often-measured environmental quantity and scientists are continuously improving ways of sensing it. To present their work in the field of temperature sensing, researchers from distant parts of the world have joined their efforts and contributed their ideas according to their interest and engagement. Their articles will give you the opportunity to understand concepts and uses of fiber-optic sensing technology. The optical fiber Mach-Zehnder interferometer for temperature sensing is presented, as well as the optical fiber-distributed temperature sensor and fiber Bragg grating-based sensor. You can learn about tunable diode laser absorption spectroscopy and its various industrial applications. Last but not least, cutting temperature measurements during the machining of aluminum alloys provides us with an insight into the correlation between cutting conditions, mechanical strength of the aluminum alloy, and the cutting temperature measured using the tool-workpiece thermocouple system. The editors hope that the presented contributions will allow both professionals and readers not involved in the immediate field to understand and enjoy the topic.